ANALISIS KESULITAN SISWA DALAM MEMAHAMI KONSEP IPAS DI KELAS II SD NO. 5 TAMAN - Putu Swistiyawati, Ni Luh; Indrayani, Ida Ayu Made (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
The aim of this research is to identify the perceptions of teachers and students in understanding the concept of science and technology learning in class II of SD No. 5 Parks. This research uses a descriptive qualitative approach. The instrument used was an interview. The subjects of this research were teachers and students of class II with a randomly selected number of students purposive sampling namely students who experience learning difficulties out of 15 students. The research location is SD N 5 Taman. Data collection procedures in this research include semi-structured interviews with teachers and students. Data were analyzed using analysis: data reduction, data presentation, drawing conclusions, and data triangulation. The results of students' understanding of science lessons vary. Some students find science lessons interesting because of their connection to nature and everyday life, while others have difficulty understanding abstract concepts such as the water cycle, weather changes, and the nature of objects. This difficulty is often influenced by the use of complex scientific terms and explanations that proceed too quickly. Teachers admit that these concepts are difficult to understand without the help of visual tools or concrete demonstrations. While visual aids such as pictures, simple models, and videos can be helpful, their effectiveness depends on each student's learning style. Obstacles faced in teaching science and technology include limited facilities and infrastructure, inadequate time allocation, and variations in students' ability to understand the material. This research shows the need for more adaptive teaching strategies and the provision of adequate resources to improve students' understanding of science lessons.